Car seatbelt use during pregnancy in Japan: determinants and policy implications. Issue 2 (1st June 2003) - Ichikawa, M; Nakahara, S; Okubo, T; Wakai, S
Abstract : Context: Pregnant women are exempted from the current seatbelt legislation in Japan despite the fact that seatbelt use is essential to reduce the risk of fatalities for these women and their fetuses in car crashes. Objective: To examine factors that might influence seatbelt use during pregnancy. Methods: A cross sectional study, with data collected via an anonymous, self administered questionnaire at obstetric clinics in suburban areas of Japan. Altogether 880 pregnant women receiving prenatal care in July 2001 were recruited. The relative effects of factors that might influence seatbelt use during pregnancy were estimated using logistic regression analysis. Results: Almost 70%–80% of pregnant women were consistent seatbelt wearers before pregnancy but seatbelt compliance was reduced by about half at 20 weeks or more gestation. Only 20% had received information on maternal seatbelt use, with one third reporting that seatbelt use is beneficial during pregnancy. Those who perceived that maternal seatbelt use is beneficial tended to maintain use, but daily car users and those who knew that they were exempted from seatbelt legislation were more likely to reduce use. Conclusions: Knowledge of the legislative exemption for pregnant women, misunderstanding of the benefits, and daily car use contributed to the reduction in seatbelt use after pregnancy.